The role of women enterprises for the conservation of Kakamega forest, Kenya - ONDIBA HESBORN ANDOLE; KENICHI MATSUI; ADWOA OFORIWA ANTWI (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This paper aims to show how local women’s community-based entrepreneurial activities have improved the management and conservation of Kakamega Forest. Recent research has shown that the western Kenyan Kakamega Forest is rapidly being cut down. In many cases, locals are held responsible for this issue. This paper, however, argues that native communities have historically played critical roles in protecting forest ecosystems.Method: Approximately 149 women from local entrepreneurship and conservation groups (chamas) were polled via questionnaire.Findings: Many of these women increased their income through forest conservation efforts. Sixty-two percent of those surveyed reported growing and domesticating wild, native plants for use as food or medicine. These actions helped protect native species while reducing ecological stress on the forest’s meager resources. Nearly 20% of people polled had a professional connection to producing eco-friendly jikos or stoves. It was hoped this would lessen the need to cut down trees for firewood.Implications/Novel Contribution: This study’s original contribution is its inquiry into the impact of women’s community-based entrepreneurial activities on the management and conservation of Kakamega Forest. It is unclear how much women’s networking and conservation initiatives have helped preserve forests.